STUDI TENTANG PERSEPSI MASYARAKAT TERHADAP ADAT UPAH-UPAH DI DESA PEMATANG BERANGAN KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Elda Wahyuni Nasution; Zahirman Zahirman; Ahmad Eddison (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research was motivated for a custom which is the original custom of Kabupaten Rokan Hulu, wherein it can be said that no matter the law, this custom must be implemented. But, in fact, this “Adat Upah-upah” is running only for several people, the remainders do not. It motivated the writer to take a title “A Study on the People’s Perception toward “Adat Upah-upah” in Desa Pematang Berangan Kecamatan Rambah Kabupaten Rokan Hulu”. The objective of the research is to find out the people’s perception toward “Adat Upah-upah” in DesaPematang Berangan Kecamatan Rambah Kabupaten Rokan Hulu. The population of the research was 353 KK, and the sample of the research was 35 persons. The instrument to collect the data were questionnaires which consist of 16 questions and interviews which consist of 4 questions. The data was analyzed by Qualitative Descriptive through percentage. Based on the calculation of percentage by respondents, the  answer “good” was obtained as 60,17% placed on rank 50,01%-75,00%. Thus, the hyphothesis which explains the people’s perception that was “good” toward “Adat Upah-upah” in Desa Pematang Berangan Kecamatan Rambah Kabupaten Rokan Hulu, was accpeted. Based on the research finding, it can be inferred that a study on the people’s perception toward “Adat Upah-upah” in Desa Pematang Berangan Kecamatan Rambah Kabupaten Rokan Hulu was good.  Keywords: Peception, “Adat Upah-upah”.